Penerapan Artificial Intelligence Menggunakan Fuzzy Logic dalam Dunia Pendidikan - Cahyaningrum, Yuniana Cahyaningrum (UNIB Press, 2023)
This research aims to apply artificial intelligence or what is commonly known as Artificial Intelligence (AI) using fuzzy logic in the world of education. The topic of artificial intelligence has become a hot and important topic of conversation today. Fuzzy logic allows processing unclear information and is used to overcome uncertainty that exists in the world of education. This article discusses the use of fuzzy logic techniques to improve the quality of education. One application of fuzzy logic is in the development of an automatic assessment system used by lecturers in providing assessments to students in the learning process. Fuzzy logic can carry out assessments objectively and enable more appropriate curriculum adjustments based on students' interpersonal skills which can ultimately increase the efficiency of the learning process. The use of fuzzy logic can provide recommendations for the learning process that can help students find material that suits their interests and needs. Fuzzy logic can be used to measure student development in social and emotional cognitive aspects. The application of AI with fuzzy logic aims to improve the quality of education and student learning experiences in the world of education.